2016
DOI: 10.1039/c6ra04041a
|View full text |Cite
|
Sign up to set email alerts
|

Organic–inorganic shape memory thermoplastic polyurethane based on polycaprolactone and polydimethylsiloxane

Abstract: We report an organic–inorganic SMP comprising PCL and PDMS that exhibits extremely fast-response time at body temperature and thermoplasticity that allows for solvent processing. The SMP recovered to the programmed shape in less than 0.5 seconds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 61 publications
3
34
0
Order By: Relevance
“…The synthesis of the urethane-based thermogelling copolymers in this work is generally similar to previous work done by our group [49,50,51,52,53]. Typically, 4 g of PEG ( M n = 2050, 2.0 × 10 −3 mol), 2 g of PPG ( M n = 2000, 1.0 × 10 −3 mol) and 0.6 g of PTHF-diol ( M n = 2000, 0.3 × 10 −3 mol) were dissolved in anhydrous toluene at 60 °C.…”
Section: Methodssupporting
confidence: 72%
“…The synthesis of the urethane-based thermogelling copolymers in this work is generally similar to previous work done by our group [49,50,51,52,53]. Typically, 4 g of PEG ( M n = 2050, 2.0 × 10 −3 mol), 2 g of PPG ( M n = 2000, 1.0 × 10 −3 mol) and 0.6 g of PTHF-diol ( M n = 2000, 0.3 × 10 −3 mol) were dissolved in anhydrous toluene at 60 °C.…”
Section: Methodssupporting
confidence: 72%
“…The T m was used as the trigger temperature for shape recovery thus achieving a T m close to the human body temperature which is very desirable for material intended to be used as biomedical material. The obtained result is consistent with a previous study, where the fabricated shape memory polymer showed a similar T m around 38 °C [ 13 ].…”
Section: Resultssupporting
confidence: 92%
“…The copolymer solutions were prepared at 10 wt% (w/w) diluted in HFIP and electro-spun at 10 kV. In general, with an appropriate polymer concentration, polymers with M n > 10,000 will form continuous fibres during the electrospinning process [ 13 ]. Referring to Table 1 , all the synthesized PCL–PDMS copolymer demonstrated M n > 10,000 which is within the expected electrospinning fibre-forming range.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermoplastic shape-memory polyurethanes (SMPURs) with tunable thermal and mechanical properties have been widely investigated as they are well suited for a broad variety of processing methods. [1][2][3] SMPUR are characterized by a phase-segregated structure, in which the switching domains act as temporary netpoints, and hard domains determine the permanent shape. SMPURs provide a high deformability but exhibit low shape recovery.…”
Section: Introductionmentioning
confidence: 99%